Occupants' subjective perceptions in three activity types to naturally ventilated & air conditioned room of mixed-function office building. (August 2019) - Li, Jin; Lu, Pin; Zheng, Hailin; Wang, Wei
Abstract: As mixed-function office buildings come into fashion, it is unclear if the two common indoor thermal environment regulation methods of these buildings, i.e. air conditioning and natural ventilation, can satisfy occupants in different activity types. This study carried out a field survey in a mixed-function office building in Guangzhou, China in the summer of 2018. Questionnaires were used to collect subjective perceptions of subjects in the three most common activity types in surveyed building, including sitting, walking at 5 km/h and running at 9 km/h in air-conditioned rooms and naturally ventilated rooms, and instruments were used to record environmental and physiological data. This study identified the mean metabolic rate, thermal neutral and upper limit of the 80% acceptable operative temperatures of subjects in the said three activity types in air-conditioned rooms and naturally ventilated rooms. The upper limit of the 80% acceptable operative temperatures of subjects in the said three activity types in air-conditioned rooms were respectively 1 °C, 3.9 °C and 4.2 °C lower than that in naturally ventilated rooms. The thermal neutral and upper limit of the 80% acceptable operative temperatures of subjects in air-conditioned rooms and naturally ventilated rooms both decreased with the increase of activity intensity, while the decreasing amplitude in air-conditioned rooms was significantly wider than that in naturally ventilated rooms. This study facilitates a better understanding of occupants' subjective perceptions at different activity intensities in air-conditioned space and naturally ventilated space, and providing reference to the improvement of indoor thermal environment. Highlights: Neutral and acceptable temperatures in three activity types to AC & NV room were identified. All above temperatures decreased with the increase of activity intensity. The decreasing amplitude of acceptable temperatures was wider in AC room than NV room. Acceptable temperature of three activity types were lower in AC room than NV room.